Influence of drinking water chloroform on the oncological incidence of the population of Kirovograd region - Prokopov, V.O.; Lypovetska, O.B. (Environment & Health, 2019)
Objective: We determined the quantitative indices of the influence of chlorinated drinking water contaminated with the organochlorine compounds on cancer morbidity in order to substantiate the preventive measures to minimize this impact on the health of the population. Materials and methods: We carried out an epidemiological analysis of the data on cancer incidence among the adult population of the cities of Svitlovodsk, Alexandria, Znamenka, Kropyvnytskyi of Kirovohrad region for 10 years (2006-2015). 160 samples of drinking water from the Dnipro-Kirovohrad main water conduit and plumbing networks of investigated cities on the content of organochlorine compounds (HOS) were analyzed. We used correlation, cluster, and regression analyses (using STATISTICA 7.0 and Microsoft Excel programs) to establish the relationship between OCC and cancer incidence in the population of Kirovohrad region. Results: There is a steady increase in the oncological morbidity of the adult population of the region (an increase of 14.3%) by chloroform content in drinking water at the level of 2-3 MPC. There is a correlation connection between excess chloroform content in drinking water and tumors of the stomach and colon (r=0.9, p